Whole Genome Analysis of Genetic Alterations in Small DNA Samples Using Hyperbranched Strand Displacement Amplification and Array–CGH - Lage, José M.; Leamon, John H.; Pejovic, Tanja; Hamann, Stefan; Lacey, Michelle; Dillon, Deborah; Segraves, Richard; Vossbrinck, Bettina; González, Antonio; Pinkel, Daniel; Albertson, Donna G.; Costa, Jose; et al. (Genome Research, 2003)
Structural genetic alterations in cancer often involve gene loss or gene amplification. With the advent of microarray approaches for the analysis of the genome, as exemplified by array–CGH (Comparative GenomicHybridization), scanning for gene-dosage alterations is limited only by issues of DNA microarray density. However, samples of interest to the pathologist often comprise small clusters of just a few hundred cells, which do not provide sufficient DNA for array–CGH analysis. We sought to develop a simple method that would permit amplification of the whole genome without the use of thermocycling or ligation of DNA adaptors, because such a method would lend itself to the automated processing of a large number of tissue samples. We describe a method that permits the isothermal amplification of genomic DNA with high fidelity and limited sequence representation bias. The method is based on strand displacement reactions that propagate by a hyperbranching mechanism, and generate hundreds, or even thousands, of copies of the genome in a few hours. Using whole genome isothermal amplification, in combination with comparative genomic hybridization on cDNA microarrays, we demonstrate the ability to detect gene losses in yeast and gene dosage imbalances in human breast tumor cell lines. Although sequence representation bias in the amplified DNA presents potential problems for CGH analysis, these problems have been overcome by using amplified DNA in both control and tester samples. Gene-dosage alterations of threefold or more can be observed with high reproducibility with as few as 1000 cells of starting material.